Zinc-iodine battery based on porous organic molecular cage
Through the preparation of porous organic molecular cage separators, the problem of the multi-iodide shuttle effect in aqueous zinc ion batteries is solved, the coulombic efficiency and cycle life of the battery are improved, and high safety and excellent redox kinetics are achieved.
Patent Information
- Application Number
- CN202411113157.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-13
AI Technical Summary
During the charging process, the shuttle effect of soluble polyiodides leads to self-discharge, low Coulomb efficiency and side reactions on the surface of zinc negative electrodes. The existing diaphragm is difficult to effectively limit, and the interface compatibility of metal-organic frame materials is poor. Poor membrane uniformity limits the improvement of electrochemical performance.
Using a separator prepared by mixing a porous organic molecular cage and a film-forming agent, a separator with a suitable pore size is formed through a simple one-step process, inhibiting the shuttle effect of I3-, and improving the coulomb efficiency and cycle life of zinc-iodine batteries.
It significantly improves the Coulomb efficiency, discharge capacity and rate performance of zinc-iodine batteries, and the preparation process is simple, gentle, and easy to control, solving the problems of poor interface compatibility and film formation.
Smart Images

Figure CN119133637A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to a zinc iodine battery based on porous organic molecular cages. Background Art
[0002] As an emerging energy storage system, rechargeable aqueous zinc-ion batteries have attracted much attention due to their advantages such as high safety, low cost and eco-friendliness. Among various aqueous zinc-ion batteries, iodine cathode has a higher theoretical specific capacity (211 mAh g -1 , based on I 0 / I - conversion reaction) and a suitable redox potential (1.38 V vs Zn / Zn 2+ ), which has better reversibility and faster redox kinetics than common metal oxide materials. 2 The practical application of batteries is mainly affected by the soluble polyiodide (I 3 – , I 5 – During the charging process, the insoluble I 2 Can spontaneously communicate with I – Combine to form highly soluble polyiodides (such as I 3 - ). Subsequently, I in the electrolyte 3 - It diffuses to the negative electrode side and reacts with Zn metal, causing adverse effects such as severe self-discharge, low Coulomb efficiency, and side reactions on the zinc negative electrode surface.
[0003] Using conventional membranes, such as polyolefins and glass fibers, it is difficult to restrict the shuttling of soluble polyiodides. The functionalized membrane strategy is a direct and effective way to reduce I 3 - The shuttle effect of polyiodide is used to improve the electrochemical performance. In order to improve the wettability of polyolefin membranes, surface modification is usually carried out by introducing functional groups such as carboxyl, amino or sulfonic acid groups to increase the surface polarity and enhance the wetting properties. In order to increase the porosity of polyolefin membranes, pores such as particles, fibers or nanomaterials are usually added during the preparation process. These porogens produce pores in the membrane, and the pores can be further enhanced by removing the porogens by washing or heat treatment. At present, some researchers have used cation exchange membranes (such as Nafion membranes) to inhibit the shuttling of polyiodide through the electrostatic repulsion effect of their negatively charged sulfonate groups, but high resistance and production cost issues limit their large-scale practical application. Recently, some researchers have achieved the goal of reducing I by functionalizing metal-organic framework (MOF) membranes with suitable pore structures. 3 -The shuttling of Zn and the harmful side reactions on the Zn anode make the aqueous Zn-I 2 The battery has a high coulombic efficiency and a long cycle life [Joule 2019, 3, 1289–1300]. However, the existing MOF materials used to prepare functional membranes tend to agglomerate into large particles, which will lead to the formation of MOF-based functional membranes with poor interface compatibility, poor film uniformity, and high surface roughness.
[0004] Porous molecular cage materials have some potential advantages over metal-organic frameworks (MOFs): for example, they can be dissolved in common organic solvents, thus being able to be cast as composite materials or combined with other porous materials; porous molecules can exhibit structural mobility, allowing synergistic interactions between hosts and guests [Adv. Mater. 2016, 28, 2629–2637]. However, porous molecular cage material membranes are rarely used in energy storage devices. For example, a few researchers have proposed a polypropylene (PP) diaphragm based on an ultra-thin functional layer of porous organic cages for selective ion screening in lithium-sulfur batteries, which can selectively screen lithium ions while blocking polysulfides [Nano Lett. 2022, 22, 2030-2037]. However, the use of polyolefin diaphragm materials in zinc-ion batteries has problems such as inappropriate porosity, poor wettability, and poor thermal stability. Therefore, it is usually necessary to increase the surface polarity and enhance the wetting properties through the use of organic materials (introducing functional groups such as carboxyl, amino or sulfonic acid groups), or to add inorganic materials (porogens such as particles, fibers or nanomaterials) to enhance the pores [Adv. Mater., 2011, 23, 3066-3070].
[0005] Therefore, considering the different battery systems, simply constructing a porous organic cage functional layer on a commercial separator cannot improve the electrochemical performance of aqueous zinc batteries. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention discloses a zinc-iodine battery based on a porous organic molecular cage, which has high coulombic efficiency, excellent redox kinetics and cycle life, and high safety.
[0007] The specific technical solutions are as follows:
[0008] A zinc-iodine battery based on a porous organic molecular cage comprises a positive electrode, a negative electrode, an electrolyte and a separator. The preparation of the separator comprises:
[0009] The porous organic molecular cage, the film-forming agent and the solvent are uniformly mixed to obtain a slurry, the slurry is coated on a substrate, and the diaphragm is obtained after demoulding.
[0010] The present invention discloses a zinc-iodine battery based on a porous organic molecular cage, wherein the diaphragm used is a porous organic molecular cage-based diaphragm prepared by a specific process. The diaphragm has a suitable pore size (0.4-1.0 nm) and can effectively inhibit I 3 - The shuttling effect of zinc iodine and zinc iodine is good, and the film forming property and interfacial compatibility are good, which can significantly improve the coulombic efficiency, discharge capacity, cycle life and rate performance of zinc iodine batteries. The preparation process of the diaphragm is simple, and the film can be formed in one step. The synthesis conditions are relatively mild and easy to control.
[0011] The various porous organic molecular cages in the present invention are prepared by using known processes in the art. The structural formulas of the various porous organic molecular cages are as follows:
[0012]
[0013] Preferred:
[0014] The porous organic molecular cage is selected from one or more of CC3 porous organic molecular cage, RCC3 porous organic molecular cage, AT-RCC3 porous organic molecular cage, and FT-RCC3 porous organic molecular cage;
[0015] More preferably, it is CC3 porous organic molecular cage and / or RCC3 porous organic molecular cage;
[0016] More preferred is CC3 porous organic molecular cage.
[0017] Preferred:
[0018] The film-forming agent is selected from one or more of polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and polytetrafluoroethylene (PTFE);
[0019] Further preferably, the film-forming agent is selected from polyvinylidene fluoride and / or polytetrafluoroethylene;
[0020] More preferably, the film former is selected from polyvinylidene fluoride.
[0021] Preferred:
[0022] Based on the total mass of the porous organic molecular cage and the film-forming agent being 100%, the amount of the porous organic molecular cage added is 2 to 50 wt %;
[0023] More preferably, the amount of the porous organic molecular cage added is 4-30 wt %; more preferably, the amount added is 30 wt %.
[0024] Preferably, the solid content of the slurry is 0.05 to 1.0 g / mL; more preferably, it is 0.1 to 0.5 g / mL.
[0025] In the present invention:
[0026] The solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and hexamethylphosphoric triamide;
[0027] The substrate is selected from conventional types in the art, such as glass plate, aluminum foil, silicon wafer, etc.;
[0028] The coating thickness is 20 to 200 μm.
[0029] In the zinc-iodine battery disclosed in the present invention, there is no special requirement for the type of the positive electrode, and it can be selected from conventional types in the art, such as carbon-based materials, conductive polymers, coordination network materials, and the like.
[0030] There is no special requirement for the type of the negative electrode, and it can be selected from conventional types in the art, such as a zinc negative electrode, a coating-modified zinc negative electrode, or a three-dimensional zinc negative electrode.
[0031] The electrolyte includes a positive electrode electrolyte and a negative electrode electrolyte. There is no special requirement for the types of the two electrolytes, and they can be selected from conventional types in the art, such as ZnSO 4 Aqueous solution, ZnSO 4 +I - +I 2 One of the following: aqueous solution, halogen-containing functional electrolyte, electrolyte containing additives, salt-in-water electrolyte, solid electrolyte, etc.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The present invention discloses a zinc-iodine battery based on a porous organic molecular cage, which uses a porous organic molecular cage-based diaphragm. The diaphragm can be prepared into a film in just one step without being compounded with other thin films. The preparation process is simple, and the synthesis conditions are mild and easy to control. The diaphragm has a suitable pore size (0.4-1.0nm) and can effectively inhibit I 3 - The shuttling effect, film-forming property and interface compatibility are good, which can significantly improve the coulombic efficiency, discharge capacity and cycle life of zinc-iodine batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is the XRD pattern of the porous organic molecular cage powder prepared in Example 1;
[0035] Figure 2 The morphology and element distribution diagram of the porous organic molecular cage powder prepared in Example 1;
[0036] Figure 3 This is a physical picture of the porous organic molecular cage membrane in Example 1;
[0037] Figure 4 is the XRD pattern of the porous organic molecular cage membrane prepared in Example 1;
[0038] Figure 5 The morphology and element distribution diagram of the plane of the porous organic molecular cage membrane prepared in Example 1;
[0039] Figure 6 The morphology and element distribution diagram of the cross section of the porous organic molecular cage membrane prepared in Example 1;
[0040] Figure 7 This is a physical picture of the porous organic molecular cage membrane prepared in Example 2;
[0041] Figure 8 is the XRD pattern of the porous organic molecular cage membrane prepared in Example 2;
[0042] Fig. 9 The morphology and element distribution diagram of the plane of the porous organic molecular cage membrane prepared in Example 2;
[0043] Fig.10 The morphology and element distribution diagram of the cross section of the porous organic molecular cage membrane prepared in Example 2;
[0044] Fig.11 This is the XRD pattern of the PVDF membrane prepared in Comparative Example 1. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below in conjunction with examples and comparative examples, but the embodiments of the present invention are not limited thereto.
[0046] Example 1
[0047] Step 1, preparation of CC3 porous organic molecular cage powder. 1,3,5-benzene trimeraldehyde (0.74mmol) and (1R, 2R)-(-)-1,2-cyclohexanediamine were added to 10mL dichloromethane at a molar ratio of 4:6, and the mixed solution was fully stirred at room temperature. After reacting for 72h, the crude product was dried at 60°C for 12h to obtain the crude product. The crude product was washed with a mixed solution of methanol and chloroform (methanol: chloroform = 95:5) to obtain pure CC3 porous organic molecular cage powder.
[0048] Step 2, preparation of CC3 porous organic molecular cage membrane. 0.96g PVDF and 0.04g CC3 porous organic molecular cage powder were added to 5mL DMF, and stirred for 1h to form a uniform viscous solution. The solution was evenly coated on a glass substrate by a scraper coating method with a thickness of 150μm. After drying at 60°C for 12h, the solution was peeled off from the substrate and punched and sliced to obtain a CC3 porous organic molecular cage membrane with a diameter of 16mm.
[0049] Figure 1 This is the XRD pattern of the CC3 porous organic molecular cage powder prepared in this example, which has good crystallinity.
[0050] Figure 2 This is a scanning electron microscope morphology image of the CC3 porous organic molecular cage powder prepared in this example. The particles are evenly dispersed and have uniform particle size.
[0051] Figure 3 This is a real picture of the CC3 porous organic molecular cage membrane prepared in this example, and the surface is relatively smooth.
[0052] Figure 4 This is the XRD diagram of the CC3 porous organic molecular cage membrane prepared in this example. Since the mass fraction of the porous organic molecular cage is relatively low, the main peak is basically displayed as PVDF.
[0053] Figure 5 and Figure 6 The scanning electron microscope morphologies of the plane and cross-section of the CC3 porous organic molecular cage membrane prepared in this example and the corresponding element distribution diagrams respectively confirm that the CC3 porous organic molecules are uniformly distributed in PVDF, with a thickness of 47.5 μm, and the material has good consistency and film-forming properties.
[0054] Step 3, zinc-iodine battery assembly. After the activated carbon (YP-80F) and polyvinylidene fluoride are evenly mixed in a mass ratio of 9:1, 5 g of NMP is added and stirred for 12 hours to obtain a slurry. The slurry is then coated on carbon paper with a coating thickness of 150 μm. After drying at 60°C, it is cut into discs with a diameter of 11 mm as the positive electrode current collector. A metal zinc foil disc with a diameter of 11 mm (thickness of 100 μm) is used as the negative electrode. The porous organic molecular cage diaphragm prepared in this embodiment is directly used as a battery diaphragm. The electrolyte on the negative electrode side adopts 2M ZnSO 4 Aqueous solution, the positive electrode electrolyte is 2M ZnSO 4 +0.5M KI+0.1MI 2 Aqueous solution.
[0055] Example 2
[0056] The preparation process is basically the same as that in Example 1, except that in step 2:
[0057] The mass of CC3 porous organic molecular cage powder was replaced with 0.30 g, and the mass of PVDF was replaced with 0.70 g.
[0058] Figure 7 This is a physical picture of the CC3 porous organic molecular cage membrane prepared in this example. As the content of the porous organic molecular cage increases, the membrane gradually turns white.
[0059] Figure 8 This is the XRD pattern of the CC3 porous organic molecular cage membrane prepared in this example. The XRD peaks of the porous organic molecular cage and PVDF exist simultaneously in the figure, which proves that PVDF has successfully loaded the porous organic molecular cage.
[0060] Fig. 9 and Fig.10 The planar and cross-sectional morphologies of the CC3 porous organic molecular cage membrane and its element distribution diagrams respectively confirm that the CC3 porous organic molecules are evenly distributed in PVDF. Its thickness is 24.0 μm, and the material has good consistency and film-forming ability.
[0061] Example 3
[0062] The preparation process is basically the same as that in Example 1, except that in step 2:
[0063] The mass fraction of CC3 porous organic molecular cage powder was replaced with 0.40 g, and the mass fraction of PVDF was replaced with 0.60 g.
[0064] The XRD pattern and morphology are similar to those in Example 2.
[0065] Example 4
[0066] The preparation process is basically the same as that in Example 1, except that in step 2:
[0067] The mass fraction of CC3 porous organic molecular cage powder was replaced with 0.50 g, and the mass fraction of PVDF was replaced with 0.50 g.
[0068] The XRD pattern and morphology are similar to those in Example 2.
[0069] Example 5
[0070] Step 1, preparation of RCC3 porous organic molecular cage powder. The preparation of CC3 porous organic molecular cage powder is the same as in Example 1. Then, CC3 porous organic molecular cage powder (0.85 mmol) and sodium borohydride are added to 20 mL of a mixed solution of chloroform and anhydrous methanol (the volume ratio of chloroform and anhydrous methanol is 1:1) at a molar ratio of 3:10, and stirred for 12 hours for reduction reaction. After the reaction is completed, 3 mL of water is added to quench the reaction, and RCC3 organic molecular cage powder is obtained after washing and drying.
[0071] Step 2 is substantially the same as Example 2, except that the CC3 porous organic molecular cage powder is replaced with an equal mass of RCC3 porous organic molecular cage powder.
[0072] The zinc-iodine battery assembly process in step 3 is the same as that in Example 1.
[0073] Example 6
[0074] Step 1, preparation of AT-RCC3 porous organic molecular cage powder. The preparation of RCC3 porous organic molecular cage powder is the same as in Example 5. Then 0.5 mmol of RCC3 organic molecular cage powder is dissolved in 30 mL of acetone solution, and the mixture is allowed to stand for 12 hours to wait for the product to precipitate, and AT-RCC3 organic molecular cage powder is obtained after washing and drying.
[0075] Step 2 is substantially the same as Example 2, except that the CC3 porous organic molecular cage powder is replaced with an equal mass of AT-RCC3 porous organic molecular cage powder.
[0076] The zinc-iodine battery assembly process in step 3 is the same as that in Example 1.
[0077] Example 7
[0078] Step 1, preparation of FT-RCC3 porous organic molecular cage powder. The preparation of RCC3 porous organic molecular cage powder is the same as in Example 5. RCC3 organic molecular cage (0.18 mmol) and paraformaldehyde are added to 20 mL of methanol solution at a molar ratio of 1:20, and stirred at 70°C for 2 h. Then, the mixture is cooled to room temperature, washed and dried to obtain FT-RCC3 organic molecular cage powder.
[0079] Step 2 is substantially the same as Example 2, except that the CC3 porous organic molecular cage powder is replaced with an equal mass of FT-RCC3 porous organic molecular cage powder.
[0080] The zinc-iodine battery assembly process in step 3 is the same as that in Example 1.
[0081] Example 8
[0082] The preparation process is basically the same as that in Example 2, except that the film-forming agent in step (2) is replaced by an equal mass of PAN.
[0083] Example 9
[0084] The preparation process is basically the same as that in Example 2, except that the film-forming agent in step (2) is replaced by an equal mass of PTFE.
[0085] Comparative Example 1
[0086] 1 g PVDF was added to 5 mL DMF and stirred for 1 h to form a uniform viscous solution. The solution was evenly coated on a glass substrate by a doctor blade method with a coating thickness of 150 μm. After drying at 60 °C for 12 h, the solution was peeled off from the substrate and punched and sliced to obtain a PVDF membrane with a diameter of 16 mm.
[0087] The zinc-iodine battery assembly process is the same as that in Example 1.
[0088] Comparative Example 2
[0089] The separator is made of glass fiber. The zinc-iodine battery assembly process is the same as that in Example 1.
[0090] Comparative Example 3
[0091] Preparation of CC3 porous organic molecular cage powder is the same as in Example 1.
[0092] 50 mg of CC3 porous organic molecular cage powder was fully dissolved in 4 mL of dichloromethane. Then, the suspension was filtered using a PTFE syringe filter (0.2 μm). The suspension was then dropped onto a PP diaphragm fixed on a glass substrate and coated using a 150 μm scraper. After drying, it was punched and sliced to obtain a PP diaphragm with a CC3 organic porous molecular cage coating having a diameter of 16 mm.
[0093] The zinc-iodine battery assembly process is the same as that in Example 1.
[0094] Performance Test:
[0095] The above-assembled zinc-iodine battery was subjected to constant current charge and discharge tests on the Blue Electric system. First, the battery was charged to 1.6V to oxidize the iodine ions on the positive electrode to I 2 Next, in the voltage range of 1.6 to 0.6 V and 0.2 to 5.0 Ag -1 At a current density of (based on I 2 The initial quality of the battery was tested by constant current charge and discharge.
[0096] The assembled zinc-iodine battery is 0.2Ag -1 The battery data at the current density are shown in Table 1.
[0097] Table 1
[0098]
[0099] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.
Claims
1. A zinc-iodine battery based on a porous organic molecular cage, comprising a positive electrode, a negative electrode, an electrolyte and a separator, It is characterized in that The preparation of the diaphragm comprises: The porous organic molecular cage, the film-forming agent and the solvent are uniformly mixed to obtain a slurry, the slurry is coated on a substrate, and the diaphragm is obtained after demoulding.
2. The zinc-iodine battery based on porous organic molecular cage according to claim 1, Features: The porous organic molecular cage is selected from one or more of CC3 porous organic molecular cage, RCC3 porous organic molecular cage, AT-RCC3 porous organic molecular cage, and FT-RCC3 porous organic molecular cage; The film-forming agent is selected from one or more of polyvinylidene fluoride, polyacrylonitrile and polytetrafluoroethylene; The solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and hexamethylphosphoric triamide.
3. The zinc-iodine battery based on porous organic molecular cage according to claim 1, Features: Based on the total mass of the porous organic molecular cage and the film-forming agent being 100%, the amount of the porous organic molecular cage added is 2 to 50 wt %; The solid content of the slurry is 0.05-1.0 g / mL.
4. The zinc-iodine battery based on porous organic molecular cage according to claim 1, It is characterized in that The porous organic molecular cage is selected from CC3 porous organic molecular cage and / or RCC3 porous organic molecular cage.
5. The zinc-iodine battery based on porous organic molecular cage according to claim 1, It is characterized in that The film former is selected from polyvinylidene fluoride and / or polytetrafluoroethylene.
6. The zinc-iodine battery based on porous organic molecular cage according to any one of claims 1 to 5, Features: The porous organic molecular cage is selected from CC3 porous organic molecular cage; The film former is selected from polyvinylidene fluoride.
7. The zinc-iodine battery based on porous organic molecular cage according to claim 6, It is characterized in that Based on the total mass of the porous organic molecular cage and the film-forming agent being 100%, the added amount of the porous organic molecular cage is 4-30wt%.
8. The zinc-iodine battery based on porous organic molecular cage according to claim 6, It is characterized in that Based on the total mass of the porous organic molecular cage and the film-forming agent being 100%, the added amount of the porous organic molecular cage is 30 wt %.
